Ensuring Sustainability for UK Burns Services: Workforce Planning for Burns Consultants. Issue 3 (March 2019) - Brady, Chevonne; Edmondson, Sarah-Jayne; Murray, Alexandra
Abstract : Introduction: Workforce planning is an essential component of organizing any health service. Centralization of burns services pools expertise, although trainees can struggle to achieve adequate exposure to burns training. We aim to review current staffing levels and predict the future consultant numbers required for UK services to remain staffed with appropriately trained surgeons. Methods: We have compiled a database of all UK burns consultants. Basic demographic data, such as age and sex, were collated. Projected UK population data have been used to estimate whether the number of patients under the care of the UK burns network will change in the coming years. Access to burns fellowship training has also been factored in. Results: There are 34 burns facilities in the United Kingdom and 86 burns consultants. On average, these consultants are 13 years from retirement age. 22 will reach this age within the next decade. During this time, the UK population is expected to increase by 10%, translating to approximately another 6 consultant posts. Since there are only 2 UK recognized burns fellowships, many of the required consultants will have to seek training abroad. Conclusions: Workforce planning is essential to avoid a short fall in the number of upcoming burns consultants. Plans must be in place to anticipate additional workload with a 10% population rise. With the current struggles of NHS funding, a comprehensive review of burns workforce planning should be undertaken to ensure that sufficient numbers of trainees are completing appropriate burns-specific training and are ready to fill these posts.